Users' perception as a tool for an integrated coastal management and beach quality assessment - Magaš, Damir, ekonomist (Array, 2018)
The aim of the paper is to show a brief review of social research methods used in beach user research and coastal zone management. It is argued that this approach may effectively be used from the perspective of Integrated Coastal Zone Management (ICZM). Beaches are one of the most important factors of the sun and sea tourism, and an area where the increased users` pressure is common with the rise of tourist activity. This expansion creates increased pressure on the coastal area, the marine eco systems and, potentially, leads to a degradation of the natural environment. Social research methodsprovide an invaluable insight into the processes incentivizing beach users in respect to physical, social, economic and natural aspects of beach uses as well as of other parts of the coast, through the conceptof the user perception. The intended result is to provide a brief methodological overview of social science research methods applied to and found in literature that can be used to be better informed of the beach management decisions as an area of ICZM interest and, in this way, contributing to the overall sustainable development of the coastal zone and increasing the competitiveness of beach tourism.